5α-Reductase Inhibitors Are Associated with Reduced Risk of SARS-CoV-2 Infection: A Matched-Pair, Registry-Based Analysis. Issue 1 (26th January 2022) - Lyon, Madison; Li, Jianbo; Cullen, Jennifer; Milinovich, Alex; Kattan, Michael; Jehi, Lara; Sharifi, Nima; Klein, Eric A.
Abstract : Purpose: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a disproportionately severe effect on men, suggesting that the androgen pathway plays a role in the disease. Studies on the effect of castration and androgen receptor blockade have been mixed, while 5α-reductase inhibitor (5ARI) use in men with COVID-19 (2019 novel coronavirus) have shown potential benefits. We assessed the association of 5ARI use on risk of community acquired SARS-CoV-2 infection. Materials and Methods: A total of 60, 474 males in a prospective registry of people tested for SARS-CoV-2 between March 8, 2020 and February 15, 2021 were included. Using a matched cohort design, men using 5ARIs were matched 1:1 to non5ARI users. Independent analysis using unconditional multivariable logistic regression on the entire unmatched data set was completed for validation. Primary outcome measures were the association of 5ARI use on rates of SARS-Cov-2 positivity and disease severity. Results: Of the men 1, 079 (1.8%) reported 5ARI use and 55, 100 were available for matching. The final matched cohorts included 944 men each. Mean duration of use was 60.4 months (IQR 17–84 months). Absolute risk for infection was significantly lower in 5ARI users compared to nonusers, 42.3% (399/944) vs 47.2% (446/944), respectively (absolute risk reduction [ARR] 4.9%, OR 0.81, 95% CI 0.67–0.97, p=0.026). Unconditional multivariable logistic regression analysis of the entire study cohort of 55, 100 men confirmed the protective association of 5ARI use (ARR 5.3%, OR=0.877, 95% CI 0.774–0.995, p=0.042). Use of 5ARIs was not associated with disease severity. Conclusions: Use of 5ARIs in men without prostate cancer was associated with a reduction in community acquired SARS-CoV-2 infection.